P18 (SRS35/TgSAG4) Plays a Role in the Invasion and Virulence of Toxoplasma gondii - Hamie, Maguy; Tawil, Nadim; El Hajj, Rana; Najm, Rania; Moodad, Sara; Hleihel, Rita; Karam, Martin; El Sayyed, Sana; Besteiro, Sébastien; El-Sabban, Marwan; Dubremetz, Jean-Francois; Lebrun, Maryse; et al. (Frontiers in Immunology, 2021)
Toxoplasmosis is a prevalent parasitic disease caused by Toxoplasma gondii (T. gondii). Under the control of the host immune system, T. gondii persists as latent bradyzoite cysts. Immunosuppression leads to their reactivation, a potentially life-threatening condition. Interferon-gamma (IFN-γ) controls the different stages of toxoplasmosis. Here, we addressed the role of the parasite surface antigen P18, belonging to the Surface-Antigen 1 (SAG-1) Related Sequence (SRS) family, in a cyst-forming strain. Deletion of P18 gene (KO P18) impaired the invasion of parasites in macrophages and IFN-γ-mediated activation of macrophages further reduced the invasion capacity of this KO, as compared to WT strain. Mice infected by KO P18, showed a marked decrease in virulence during acute toxoplasmosis. This was consequent to less parasitemia, accompanied by a substantial recruitment of dendritic cells, macrophages and natural killer cells (NK). Furthermore, KO P18 resulted in a higher number of bradyzoite cysts, and a stronger inflammatory response. A prolonged survival of mice was observed upon immunosuppression of KO P18 infected BALB/c mice or upon oral infection of Severe Combined Immunodeficiency (SCID) mice, with intact macrophages and natural killer (NK) cells. In stark contrast, oral infection of NSG (NOD/Shi-scid/IL-2Rγnull) mice, defective in macrophages and NK cells, with KO P18, was as lethal as that of the control strain showing that the conversion from bradyzoites to tachyzoites is intact and, suggesting a role of P18 in the response to host IFN-γ. Collectively, these data demonstrate a role for P18 surface antigen in the invasion of macrophages and in the virulence of the parasite, during acute and chronic toxoplasmosis.